2017
DOI: 10.1007/s00380-017-0962-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of factor-Xa inhibitors in Japanese patients with atrial fibrillation

Abstract: Activated factor-X (FXa) plays an important role not only in the coagulation cascade, but also in pro-inflammatory responses. However, few data exist regarding the anti-inflammatory effect of FXa inhibitors in clinical practice. The aim of this study was to evaluate the anti-inflammatory and anti-atherosclerotic effects of FXa inhibitors in Japanese patients with non-valvular atrial fibrillation (NVAF). Eighty-three patients with NVAF were treated with FXa inhibitors from March 2013 to March 2015 at our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…In the clinical setting, however, the anti-inflammatory effect of DOAC was still controversial. 9,21 In the present study median hsCRP was significantly reduced (0.03 mg/dL; IQR, 0.02-0.04 mg/dL, P<0.001) 6±3 months after initiation of DOAC therapy. Treatment was not basically changed between pre-and post-DOAC hsCRP assessments, except for initiation of the DOAC.…”
Section: Anti-inflammatory Effect Of Doacsupporting
confidence: 49%
“…In the clinical setting, however, the anti-inflammatory effect of DOAC was still controversial. 9,21 In the present study median hsCRP was significantly reduced (0.03 mg/dL; IQR, 0.02-0.04 mg/dL, P<0.001) 6±3 months after initiation of DOAC therapy. Treatment was not basically changed between pre-and post-DOAC hsCRP assessments, except for initiation of the DOAC.…”
Section: Anti-inflammatory Effect Of Doacsupporting
confidence: 49%
“…Importantly, the anti-inflammatory effects of FXa inhibitors have been demonstrated in human subjects. For example, the anti-inflammatory effects of rivaroxaban and apixaban were recently observed in Japanese patients with atrial fibrillation [64]. The anti-inflammatory effect of apixaban was also recently demonstrated in the acute phase of ischemic stroke patients [65].…”
Section: Anti-inflammatory Activity Of Direct Fxa Inhibitorsmentioning
confidence: 97%
“…In the past few years, many researchers postulated a strong relationship between coagulation cascade and several nonhematological pathological conditions. The pathological role of coagulation system has been recognized in different inflammatory diseases . Davalos and Akassoglou reported that fibrinogen is a potent proinflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…Factor Xa was reported to stimulate the production of the proinflammatory and profibrotic mediators by retinal pigment epithelial cells. [29] Interestingly, Katoh et al recently showed that the beneficial effect of factor Xa inhibitors in atrial fibrillation clinically is attributed not only to direct antithrombotic effect but also to their anti‐inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%